Characteristic of silica nanoparticles on mechanical performance and microstructure of sulphoaluminate cement/ordinary Portland cement binary blends. (10th May 2020) - Li, Guoxin; Liu, Qingfeng; Niu, Mengdie; Cao, Li; Nan, Bing; Shi, Chen
Highlights: Nanosilica accelerates the early hydration process of CSA-OPC blends. A small dosage of nanosilica significantly enhances the strength of composites. Nanosilica helps to form a denser microstructure with binary blends. Abstract: Nanosilica (NS) with ultra-fine structure and high pozzolanic activity frequently used to reinforce cement-based materials. In this study, NS was selected to modify CSA-OPC blends to meet the critical engineering properties of rapid repair materials, such as fast setting hardening, high early strength and sustainable late strength. The effects of NS on the setting time, mechanical strength, phase and mass change of hydrates and pore structure of binary blends were investigated. Results indicated that NS largely shortens the setting time. The remarkable enhancement in the early strength compared to other substitution levels by adding 1.0wt. %NS, and the sustainable late strength was maintained. XRD and TG-DTA demonstrate that ettringite was the main hydrate and its content evidently increase with the inclusion of NS. Furthermore, SEM micrographs was observed that NS effectively improves the binding between the hydrates. The utilization of NS resulted in less porosity and more homogeneous binary mortar as seen in MIP test.